Fertility of N'dama and Bunaji cattle to artificial insemination following oestrus synchronization with PRID and PGF2a in the hot humid zone of Nigeria - Voh, A.A.; Larbi, Asamoah; Olorunju, S.A.S.; Agyemang, K.; Abiola, B.D.; Williams, Timothy O. (2004)
A study was undertaken to determine the effectiveness of a progesterone-releasing intravaginal device (PRID) and prostaglandin F2 alpha (PGF2a) in synchronizing oestrus in N'dama and Bunaji cows and heifers and the fertility following artificial insemination at the synchronized oestrus. A total of 116 cows and heifers (58 N'dama and 58 Bunaji) were used in two separate trials. In the first trial, oestrus was synchronized using a PRID, which was inserted for 12 days; in the second trial, oestrus was synchronized by giving two injections of PGF2a 13 days apart. Only animals that did not respond to the first injection were given the second injection. At the end of each treatment period, the animals were observed for oestrus for 7 days and inseminated approximately 12 h following detection of oestrus. Standing to be mounted was the single criterion used to judge an animal to have been in oestrus. PGF2a and PRID were both effective in synchronizing oestrus in N'dama and Bunaji cows and heifers. The respective oestrus response rates, pregnancy rate and conception rates for PRID and PGF2a were 85.7%, 53.6% and 62.5% for PRID, and 91.7%, 68.3% and 74.6% for PGF2a. N'dama cattle showed significantly (p<0.05) better oestrus response rate, pregnancy rate and conception rate than Bunaji cattle following both PRID and PGF2a treatments. The pregnancy rate and conception rate following PGF2a treatment were better (p<0.05) than for PRID, although the oestrus response rate did not differ. It is concluded that both PRID and PGF2a are effective in synchronizing oestrus in N'dama and Bunaji cattle in the hot humid zone of Nigeria and the fertility to artificial insemination at the synchronized oestrus was normal and acceptable. Thus, PRID and PGF2a can effectively be used in intensive breeding programmes for the rapid multiplication and distribution of both cattle breeds, especially the N'dama, which is a unique and beneficial animal genetic resource for the tsetse infested hot humid zone of Nigeria.